UPAYA MENINGKATKAN GOOD CORPORATE GOVERNANCE DENGAN PENETAPAN HOSPITAL BYLAWS/STATUTA DI AMAL USAHA KESEHATAN MUHAMMADIYAH/AISYIYAH JAWA TIMUR - M. Natsir Nugroho; Aliyus Kusumaningrum (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
This paper is a review of the literature and application of good corporate governance which is regulated through the Hospital Bylaws / Statute of hospitals in the Muhammadiyah charitable efforts, particularly in order to reduce conflicts of interest between the owners, founders, managers and implementers of the healthcare. Hospital By laws regulate care services authority, responsibility of three important organs, governing board, chief executive office (CEO) / director, the medical staff. The implementation based on the results of case studies in Amal Usaha Kesehatan Muhammadiyah / Aisyiyah East Java in centrally coaching by MKKM as the governing board of East Java region has been able to improve performance of Aumkes Muhamadiyah / Aisyiyah to be more advanced.